The Impact of Technological Change and Lifestyles on the Energy Demand of Households. A Combination of Aggregate and Individual Household Analysis - Kurt Kratena; Ina Meyer; Michael Wüger (Austrian Institute of Economic Research (WIFO), 2009)
This paper deals with integrating technology as well as lifestyles as driving forces of energy demand into a model of total private consumption. Private consumption is determined by economic variables like income and prices as well as these other factors. Technology is represented by variables measuring the efficiency of households' capital stocks and lifestyles by socio-demographic variables. Data for both types of variables are available in cross section consumer surveys and in time series data of aggregate consumption. The cross section surveys provide information on income and socio-demographic factors relevant for energy demand (characteristics of building and population density). The time series data contain information on prices and income as well as the energy efficiency embodied in household appliances. The final model of consumption consists of a consistent combination of both time series and cross section information into one comprehensive econometric model. This model describes demand for energy and non-energy commodities in an almost ideal demand system (AIDS) and is used in ex-post simulation exercises to isolate the impact of technological and socio-demographic variables on the demand for gasoline/diesel, heating and electricity.
Keywords: 330; household energy demand; rebound effects; efficiency of appliances; lifestyles; Energiekonsum; Privater Haushalt; Lebensstil; Technische Effizienz; Gesamtwirtschaftliche Nachfrage; Österreich